Trans “enough” for protection? Experimenting with credibility in refugee status determination - Hertz, Maya Ellen; Jarlner, Asta Sofie Stage (Frontiers in Human Dynamics, 2025)
This study analyzes how the credibility of transgender asylum claimants in the Danish asylum system is assessed by decision makers. The analysis takes an empirical mixed methods approach to investigating how credibility of transgender asylum claimants is evaluated. By combining statistical analysis of a dataset with ~15,000 case summaries from the Danish Refugee Appeals Board and results from an original experimental study, we present three key findings. First, our study finds a rise in the number of claims based on sexual orientation and gender identity (SOGIE) over time, underscoring the need for a better understanding of how these claims are assessed. Second, results from our experimental study indicate that transgender claimants who have had gender-affirming medical intervention in their transition are more often deemed credible and granted refugee status. Furthermore, the experimental study observes that women and LGBT+ participants are more likely than men and non-LGBT+ participants to deem a claimant’s narrative credible and grant them refugee status. These findings suggest that transnormative ideas of how a transgender claimant ‘legitimately’ transitions has an effect on decision makers’ credibility assessments, and that the background characteristics of the decision maker has a systematic effect on their decision-making. In the article, we critically reflect on the consequences of relying on stereotypes to assess a claimant’s credibility, both in terms of non-compliance with international guidelines and of risking unjust outcomes for asylum claimants.